Case report: Short-course hypofractionated radiation therapy combined with immune checkpoint inhibitors for the treatment of advanced ovarian mucinous cystadenocarcinoma - Wan, Xinan; Fang, Mingxing; Yuan, Le; Zhang, Hang; Wang, Dan (Frontiers in Oncology, 2025)
BackgroundOvarian mucinous cystadenocarcinoma is a rare subtype of ovarian epithelial carcinoma that is resistant to platinum-based chemotherapy and has a poor prognosis, and there is no standard treatment plan for patients for whom multiline treatment has failed.Case presentationoma with FIGO stage IVB disease who was sequentially treated with paclitaxel liposomes+carboplatin, 5-Fu+CF+oxaliplatin, capecitabine+oxaliplatin, bevacizumab+FOLFOX4, S-1, and bevacizumab+oxaliplatin+raltitrexed chemotherapy. After the progression of the disease, a combination of short-course hypofractionated radiation therapy and immune checkpoint inhibitors was used. The radiotherapy target area was the metastatic lymph nodes in the right posterior part of the hepatic artery, with a radiation dose of 30 Gy/10 F. Camrelizumab, an immune checkpoint inhibitor, was administered intravenously every three weeks at a dose of 200 mg each time. The therapeutic effect was significant, with CA125 levels within the normal range. Metastatic lymph nodes disappeared from the abdominal cavity. The therapeutic effect achieved a complete response (CR). Currently, CA125 levels are within the normal range, and abdominal CT reveals no tumor recurrence or metastasis. The duration of response (DoR) reached over four years.ConclusionOvarian mucinous cystadenocarcinoma is a rare tumor with poor treatment efficacy and poor prognosis. Short-course hypofractionated radiation therapy combined with PD-1 inhibitors may be an effective and safe treatment strategy.